Aharonov-Bohm effect in scattering of high-energy particles - Sitenko, Yu.A.; Vlasii, N.D. (Вопросы атомной науки и техники, 2012)
Quantum-mechanical scattering of coherent high-energy charged particles by a magnetic vortex is considered. The vortex core is assumed to be impermeable to scattered particles, and effects of its transverse size are taken into account. The limit of high energies of scattered particles corresponds to the quasiclassical limit, and we show that in the scattering the Aharonov-Bohm effect persists in this limit owing to the Fraunhofer diffraction in the forward direction. The issue of the experimental detection of the Fraunhofer diffraction peak and the Aharonov-Bohm effect in the quasiclassical limit is discussed. Рассматривается квантово-механическое рассеяние высокоэнергетических заряженных частиц магнитным вихрем. Ядро вихря предполагается непроницаемым для рассеиваемых частиц, и учитываются эффекты его поперечных размеров. Предел высоких энергий рассеиваемых частиц соответствует квазиклассическому пределу, и мы показываем, что эффект Ааронова-Бома в рассеянии в этом пределе выживает благодаря дифракции Фраунгофера в направлении вперед. Обсуждаются вопросы экспериментального детектирования пика Фраунгоферовой дифракции и эффекта Ааронова-Бома в квазиклассическом пределе. Розглядається квантово-механічне розсіяння високоенергетичних заряджених частинок магнітним вихором. Припускається, що ядро вихора є непроникним для розсіюваних частинок, та враховуються ефекти його поперечних розмірів. Границя високих енергій розсіюваних частинок відповідає квазікласичній границі, і ми показуємо, що ефект Ааронова-Бома в розсіянні в цій границі виживає завдяки дифракції Фраунгофера в напрямку вперед. Обговорюються питання експериментального детектування піка Фраунгоферової дифракції та ефекта Ааронова-Бома в квазікласичній границі.